Transitional stages of thin air film entrapment in drop-pool impact events. (25th October 2020) - Mirjalili, Shahab; Mani, Ali
Abstract: Abstract : During the early stages of drop-pool impacts, an air film is temporarily entrapped between the liquid bodies. At low impact velocities, this film can become highly stretched, allowing for contact-free penetration of the drop into the pool. The elongated film never ruptures for the lowest impact velocities, resulting in drop bouncing. For higher impact velocities, the elongated film ruptures to entrain hundreds of micro-bubbles in a process known as Mesler entrainment. At even higher impact velocities, an elongated film never forms as early contact entraps a shorter disk-type film which retracts to one or few central bubbles. In this work we use numerical simulations of water drop-pool impacts along with theoretical analyses to discover a capillary transition that prevents early contact. This transition allows the drop to penetrate further into the pool and provides a pathway for the formation of elongated films. Since Mesler entrainment is only possible if early contact is prevented, we use the occurrence of transition as a criterion to provide an upper boundary for the Mesler entrainment regime. We observe from low $We$ simulations that after transition, the drop spreads on the pool surface, during which the minimum film thickness increases and the film regularizes. Interestingly, we observe the formation of kinks between the centre of the film and the spreading fronts, and find asymptotic scaling laws governing the film thickness. Lastly, by examining the role of liquid viscosity, we shed light on transition dynamics for different liquids.